Performance of Waste Tire Activated Carbon on Methylene Blue - MANIOM, MATHURAMBIGA; R. Gunasegaran, Yahsiga (Multidisciplinary Applied Research and Innovation, 2023)
Waste tire was chosen as a raw material to synthesize activated carbon through physical and chemical activation methods and to evaluate the performance of methylene blue treatment. Physical activation method was done by heating the waste tire in the furnace at 600˚C and the chemical activation was done by using phosphoric acid  Prepared waste tire activated carbon (WTAC) was analyzed using Fourier-transform Infrared Spectroscopy (FTIR) to determine the presence of functional group and their composition. Methylene blue (MB) was chosen as a dye that can be considered as a major pollutant in textile industries’ wastewater. It is a toxic and carcinogenic dye that is harmful to organisms that are exposed to or consumed. The adsorption method using WTAC was used to treat methylene blue due to its higher MB removal efficiency. In this research, methylene blue samples were treated using different dosages of WTAC (5g & 10g). Colour removal (CR%) analysis and COD analysis were done to evaluate the performance of WTAC on methylene blue treatment. 97.68% and 98.03%  of colour removal (CR%) were achieved using WTAC dosages of 5g and 10g respectively. For COD analysis, 35.97% and 53.23% of COD removal (%) were achieved when 5g and 10g of WTAC dosages were used. Hence, adsorption of MB increases when the dosages of WTAC increases due to more exchangeable sites or surface areas present in the sample.